Kościół w Panamie w przededniu Światowych Dni Młodzieży w 2019 roku - Stelmach, Dawid (Annales Missiologici Posnanienses, 2019)
The announcement of Panama as host of World Youth Day in 2019, turned out to be a great surprise for the whole world. For the fi rst time such a small country, has hosted a global event. Panamá is known primarily from the Panama Canal and the Panamanian aff air called Panama. But speaking in these two contexts is very hurtful, because it is a country richly diverse, and the Church here has a unique, unique face. Catholic missions are included in the history of Panama from the very beginning. From the beginning of the bishopric in the city of Panamá, through the territorial development of the Church, everything here has a mark of mission. The fi nal element of the article is the presentation of the Church in the Bocas del Toro Territorial Prelature. The prelature is located in the Caribbean Sea and is geographically diff erent from the rest of the country. But this place is an example of a missionary church, and of a church that needs support in its mission. Poles coming to Panama for the next World Youth Day will discover a unique country, and together with the Poles, Panama will be discovered by the whole world.